COMPLICAÇÕES ENCONTRADAS DURANTE O PERÍODO GESTACIONAL DEVIDO O USO ABUSIVO DA COCAINA: REVISÃO LITERÁRIA (REMUNOM, 2023)
Abstract: Cocaine use is a serious public health problem worldwide. In pregnant women, this situation is more delicate as it takes on greater proportions, considering that exposure to drugs in this group of people can cause several problems for the integrity of both the mother and the newborn.objective: of this article was to identify the risks of cocaine use during pregnancy, for fetuses, newborns and pregnant women. Methods: Medline (Medical Literature Analysis and Retrieval Systen Online), Lilacs (Latin American and Caribbean Literature in Health Sciences), Google Scholar and the Nursing Database (BDENF) were used as research tools. Conclusion: The effects of cocaine on the fetus can be catastrophic, worsened by the socio-environmental conditions present in socially neglected populations. It is associated with an increased incidence of spontaneous abortions, premature births, restricted intrauterine growth and low birth weight newborns and cardiorespiratory problems, which increase the risk of fetal and infant mortality.